Formative Assessment with eRubrics: an Approach to the State of the Art - Cebrián-de-la-Serna, Manuel; Bergman, María (Redu, 2014)
Today there is no longer any doubt about the benefits of technology for university teaching, especially in relation to the socialisation of knowledge, communication and partnerships, among other important goals. Clearly, technology increasingly represents equipment and services that are crucial for teaching. However, despite the current general impact of technology, there are certain teaching areas, such as the evaluation of learning, where teachers cannot be replaced by technology (e.g. evaluating texts). The role of teachers in creating quality-learning environments, together with the students’ commitment in every stage of their learning process, is essential in order to make the most of technology. The present case study aims to promote the use of technology in general assessment and sets the following specific objective: to share successful practice and research on the use of eRubrics (i.e. electronic rubrics) in the field of assessment of university learning. The starting point is the need to strengthen certain skills among teachers and students, while building communities of practice on their use.
Keywords: Enseñanza superior - Innovaciones tecnológicas; Enseñanza asistida por ordenador; Rubric; Performance Based Assessment; Higher Education